Drunk driving offenders' knowledge and behaviour in relation to alcohol-involved driving in Yinchuan and a comparison with Guangzhou, China. (April 2016) - Jia, Keqin; King, Mark; Fleiter, Judy J.; Sheehan, Mary; Ma, Wenjun; Lei, Jing; Zhang, Jianzhen
Highlights: We conducted survey among drunk driving offenders in two Chinese. Drunk driving offenders had a low level of knowledge about two legal BAC limited levels. Drunk driving offenders had limited knowledge about how much to drink are safe if driving. The alcohol misuse problems in both cities were serious. Abstract: Objective: This study was conducted after a legislative amendment criminalising drunk driving (BAC > 80 mg/100 ml) had been in force for a year and investigated whether drunk driving offenders in Yinchuan, China were aware of the law, and whether their knowledge of and exposure to enforcement and the existence of alcohol use disorders were related to their alcohol-involved driving behaviour. The results were compared with results from an earlier study in Guangzhou, China. Method: A survey was conducted from July to October 2012 in Yinchuan to collect information on drunk driving offenders' knowledge and practice in relation to alcohol-involved driving. The Alcohol Use Disorders Identification Test (AUDIT) was used to assess hazardous drinking levels. In total, 106 drunk driving offenders were recruited while in detention. The findings were compared with those of the Guangzhou study, where the same procedure was used to recruit 101 drunk driving offenders. Results: The mean age of the sample was 31.7 years (SD = 8.1; range 17–59 years). Males constituted 96% of the sample. The mean age at which offenders reported starting to drink alcohol was 18.7 years (SD = 3.2; range 10–26 years). Driver's licenses had been held for an average of 8.5 years. The status of knowledge in relation to alcohol-involved driving in Yinchuan was slightly lower in proportion than in Guangzhou. The rate of alcohol-involved driving reported in the previous 12 months in Yinchuan (43%) was slightly higher than in Guangzhou (39%). The proportion of recidivists in Guangzhou (21.8%) was higher than Yinchuan's (10.4%). On average, offenders had experienced 1.6 police alcohol breath tests in the previous year (SD = 1.3; range 1–10). AUDIT scores indicated that a substantial proportion of the offenders had high levels of alcohol use disorders. Discussion: Limited awareness of legal alcohol limits might contribute to drunk driving offences. The high level of alcohol consumption by many offenders suggests that hazardous drinking levels may be a contributor. Recidivist drivers also had higher AUDIT scores, which suggest there may be benefit in using the AUDIT to identify potential drink drivers and recidivists, subject to further research.